ORGANISASI UMAT ISLAM INDONESIA DI KOREA SELATAN (Pengenalan, Masalah, dan Tantangan)* - Sonezza Ladyanna (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2014)
AbstractThe purpose of this article is to explain the problems and challengesfaced by the organization which is established by the Indonesian Moslem in South Korea. Thus, the issues of this research; what are the Islamic organizations from Indonesia in South Korea, what are the activities of the organization, and what problems and challenges are faced by the organization. Qualitative study is conducted (2012-2014). Data are collected through direct observation, archives of the organization, and interviews with the chairman and board as well as Islamic organization and Indonesian Moslem in Korea. Then, the data is analyzed and reported in a descriptive qualitative. There are two Islamic organizations, they are IMUSKA and KMI, under KMI also has other organizations which are located in the mushalla and the mosque. IMUSKA intended for students and professionals, KMI is devoted to labor. However, the IMUSKA and KMI are interrelated. Problems which encountered by IMUSKA and KMI are the distribution of management domiciles and members with far distance. The challenge that they face is to bring Indonesian Moslem back to the right path.Keywords: Islamic organization, Indonesia, Korea.